USING ENGLISH TO PRESERVE THE LITHUANIAN NATIONAL HERITAGE IN AUSTRALIA - TAŠKŪNAS, ALGIMANTAS PATRICIJUS (Knygotyra, 2015)
Until World War II, there were few Lithuanians in Australia. Their numbers were boosted when 10,000 Lithuanian refugees arrived in this country in the late 1940s and early 1950s. Many congregated in the larger cities and established the structures necessary for the preservation of their national identity. These structures included Lithuanian newspapers and books, weekend schools, choirs and folk-dancing groups, Lithuanian libraries, credit unions, etc. All these initiatives were aimed at preserving the Lithuanian heritage, the “lietuvybė”, and were addressed at the Lithuanian-speaking newcomers. These former refugees were still passionately hoping for an early liberation of their homeland, especially in their early years in Australia. At the same time, prompt assimilation of the European immigrants was in the forefront of the Australian Government’s policy. Most Lithuanians managed to meet the Government’s requirement without losing their “lietuvybė” – an interesting phenomenon that has been studied in its own right and needs further in-depth discussion. In spite of the significant input by 10,000 Lithuanian migrants, however, the Australian population at large knew very little, or nothing at all, about Lithuania and its people. The Australian Lithuanians, aided by their Baltic colleagues, belatedly realised that it was not enough to document the Lithuanian identity and heritage just in Lithuanian. All about the Lithuanians, and the other Balts, had to be made known to Australians, in English. As a short-term measure, new newspapers, bulletins, leaflets and media releases were produced in English, featuring the facts of the foreign rule in the Baltics. Books started appearing on similar topics. In Australia today, some of the Lithuanian heritage continues to be recorded and published, in English. However, this work is carried out piecemeal and under difficul conditions. There is only one English-language Lithuanian journal in Australasia and in the whole Southern Hemisphere (Lithuanian Papers). Over 30 English-language books published in Australia during the past 50 years describe Lithuania and its people. Some are devoted entirely to this topic. Others have merely a chapter or two on Lithuania. Whether lengthy or brief, a number of these volumes are of a high standard; but several others are erroneous and misleading.